A Party with Purpose: To Strengthen the Role of Women in Politics (1976)
This brochure announces a July 11, 1976 event at the Metropolitan Opera House in New York City, held on the eve of the Democratic National Convention, titled "A Party With a Purpose." The event aims to strengthen the role of women in politics by supporting the National Women's Political Caucus' Democratic Task Force and spotlighting the Democratic Women's Agenda, while honoring women delegates. Featuring celebrity emcee Candice Bergen and a long list of prominent political and cultural figures, the fundraiser includes cocktails, entertainment, and opportunities to meet presidential contenders and women political leaders.